Nursing focuses and interventions that promote the autonomy of the elderly - Andreia Maria Novo Lima; Maria Manuela Ferreira da Silva Martins; Maria Salomé Martins Ferreira; Adriana Raquel Neves Coelho; Soraia Dornelles Schoeller; Vítor Sérgio Oliveira Parola (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objectives: To describe the meaning attributed to the experiences of the clinical experience of specialist nurses in the implementation of nursing care focuses and respective interventions that promote the autonomy of the elderly. Method: Qualitative study based on Giorgi's method. Eighteen specialist nurses were interviewed, recruited for convenience in two hospitals in the northern region of Portugal, between March and December 2018. Results: In the clinical experience of specialist nurses, regarding the nursing process, three themes emerged: focuses of nursing care; implementation of nursing interventions and hindering factors. Conclusions: The specialist nurses, most of whom are rehabilitation specialists, essentially promote the physical capacity of the elderly, within the scope of autonomy, revealing that working conditions, such as lack of time and information systems, are the limiting factor of their promotion.